Description of the mpox virus infection outbreak (formerly known as monkeypox) in Spain, April-December 2022 (Boletín Epidemiológico Semanal, 2023)
Introduction: Mpox infection (formerly known as monkeypox) is an endemic zoonosis in West and Central Africa. In May 2022, the first cases without a history of travel or contact with confirmed cases appeared in Europe, leading to a large outbreak that has been declared as a Public Health Emergency of International Concern (PHEIC) by the World Health Organization. Method: Descriptive analysis of the epidemiological, clinical, and exposure-related characteristics of the cases affected by the mpox outbreak during April-December 2022 in Spain, reported to the National Surveillance Network.Results: A total of 7.498 confirmed cases of mpox infection were recorded, being Madrid and Catalonia the most affected regions. The majority of cases were Spanish men. The peak of the epidemic curve was reached during the 27th epidemiological week with 784 cases. Patients presented with general symptoms reached a 71,8% while a 63,1% showed anogenital rash; significant differences in clinical presentation were observed by sex and age. In 82,4% of cases, transmission was attributed to sexual contact. A representative 8,7% of cases had complications, 3,7% were hospitalized, and there were three deaths.Conclusions: The mpox outbreak in Spain has presented a great magnitude, being the first country in Europe and the third in the world in terms of number of cases. Unlike previous outbreaks, the profile of those affected was of a young adult male with predominantly sexual transmission. Overall, the clinical course was favourable, although a few deaths were recorded.
Keywords: mpox infection; outbreak; surveillance